Analisis Bibliometrik Pengelolaan Sampah Plastik Laut di Indonesia - Nurhaerani Tenriwaru; Umi Umairah Suhardi; St. Amaliah Ramli (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Marine debris, especially plastic debris, is a global problem that requires intensive monitoring and management due to its impacts on humans, nature, and the environment. Indonesia, as the world's second-largest contributor to marine plastic debris, has committed to reducing marine plastic debris by 70% by 2025 by developing a National Action Plan (RAN) for Marine Debris Management. The abundance of plastic debris in Indonesia's marine environment has attracted global attention from scientists, and it is important to review research progress and predict research trends in this field. This study aims to determine marine debris management in Indonesia. To achieve this goal, researchers collected publications related to marine debris from the last five years obtained from the Scopus search database and analyzed them using VOSviewer. Based on the findings, publications related to marine plastic debris in Indonesia are still low, despite this issue being of great transboundary importance. This study also has limitations, namely, the data used in this study are research data from 2020 to 2024. Recommendations for further research include examining the correlation between Marine Debris and international cases from a different perspective.